2017
DOI: 10.1002/1873-3468.12698
|View full text |Cite
|
Sign up to set email alerts
|

Perfecting prediction of mutational impact on the aggregation propensity of the ALS‐associated hnRNPA2 prion‐like protein

Abstract: An increasing number of human proteins are being found to bear a prion-like domain (PrLD) driving the formation of membraneless compartments through liquid-liquid phase separation. Point mutations in these PrLDs promote the transition to an amyloid-like state. There has been much debate on whether this aberrant aggregation is caused by compositional or sequential changes. A recent extensive mutational study of the ALS-associated prion-like hnRNPA2 protein provides a framework to discriminate the molecular dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 16 publications
1
8
0
Order By: Relevance
“…They can be single or multiple residues substitutions, as well as deletions and insertions. It exploits the highly significant correlation between the scores obtained from a parameterized linear function, that balances the contribution of both PrLDs composition and amyloid propensity [13], and the intracellular aggregation of hnRNPA2 variants; the unique prion-like protein for which a large set of mutations, both natural and artificial have been experimentally validated (Fig. 1a).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…They can be single or multiple residues substitutions, as well as deletions and insertions. It exploits the highly significant correlation between the scores obtained from a parameterized linear function, that balances the contribution of both PrLDs composition and amyloid propensity [13], and the intracellular aggregation of hnRNPA2 variants; the unique prion-like protein for which a large set of mutations, both natural and artificial have been experimentally validated (Fig. 1a).…”
Section: Methodsmentioning
confidence: 99%
“…1Correlation between AMYCO and pRANK predictions and the aggregation propensity of human hnRNPA2 prion-like protein variants. a Graphic representation of the correlation between the mutants' AMYCO ( a ) and pRANK ( b ) scores and their ability to form prionic colonies (Ade+) when expressed in yeast, a direct reporter of their aggregation propensity [13]…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…An increasingly recognized process being implicated in several neurodegenerative diseases is the formation of membraneless liquid droplet-like organelles by the proteins containing prion-like domains through a process called liquid-liquid phase separation (LLPS) (Figure 5) (Shin and Brangwynne, 2017). Several RNA binding proteins like TDP-43, FUS, hnRNPA1 and hnRNPA2/B1 etc., contain intrinsically disordered regions and can undergo phase separation through transient intermolecular interactions (Burke et al, 2015; Lin et al, 2015; Molliex et al, 2015; Patel et al, 2015; Conicella et al, 2016; Batlle et al, 2017; Gopal et al, 2017; Li et al, 2017; Sun and Chakrabartty, 2017; Uversky, 2017). Proteins with a prion-like low complexity domain (LCD), exhibit in this region, an over-representation of polar and charged amino acids including arginine, lysine, glutamine, serine, glutamic acid and occasionally glycine, alanine and proline with interspersed aromatic residues, particularly tyrosine and phenylalanine (Shin and Brangwynne, 2017).…”
Section: Aggregation Of Tdp-43mentioning
confidence: 99%
“…A subsequent reanalysis of our data set showed that PrionW is also reasonably effective at predicting prion activity in yeast for our mutants, and that combining PrionW and PAPA may further improve prediction accuracy. 15 PrionW differs from PAPA in that it combines amino acid composition analysis with a position-specific matrix to identify predicted amyloid-prone segments. 16 Other algorithms show varying degrees of predictive success.…”
Section: Rationally Manipulating the Aggregation Activity Of A Human mentioning
confidence: 99%